Criterion to find examples Of some implicit moral concepts in the Quran - ali modaber; Zahra Gholami (اخلاق وحیانی, 2024)
Some important moral teachings that are widely mentioned in the traditions of the Ahl al-Bayt, peace be upon them, are not specified by their names in the Holy Qur'an, and apparently, they are not found in the teachings and rulings of the Holy Qur'an. On the one hand, their importance requires that they be mentioned in the Holy Quran (as Taqqal Akbar) and on the other hand, their widespread reflection in the traditions shows the presence of these teachings in the Holy Quran. because the narrations of Ahl al-Bayt (peace be upon them) are taken from the Holy Quran.This article is responsible for stating a criterion for obtaining examples of such moral concepts in the Qur'an, and for example, it is in pursuit of criteria to obtain examples of the social principle of "tolerance" and has reached the following results: 1. Although in the Qur'an The word "tolerance" is not mentioned in the Holy Qur'an, examples of tolerance are mentioned in the Holy Quran (at least twenty examples). 2. To identify Quranic examples of tolerance, there are criteria that can be used to identify the mentioned examples. 3. It is possible to identify examples of tolerance with the help of the "semantic gem of tolerance" and "interpretive narratives". 4. It is not possible to get access to examples of tolerance through the clarification of the commentators and translators of the Qur'an, and they can only be used to the extent of "confirmation". The research method in this article is descriptive-revealing, its information processing (data processing) is explanatory and analytical, and its information gathering method is library.